Pra-Rancangan Pabrik Nanoaspal dari Asbuton Kapasitas 80.000 Ton/Tahun - ALFARISYI, GIOVANNI; FAKHRI, ISMAIL; P, RINY YOLANDHA (e-Proceeding FTI, 2024)
PT XYZ is a company that produces nanoasphalt from asbuton using Sorbitan Monooleate (SPAN 80) surfactant. As one of the pioneers of the nanoasphalt industry in Indonesia, to meet domestic needs for nanoasphalt with a designed capacity of 80,000 tons/year. In addition to making Nanoasphalt as the main product, PT XYZ also provides SPAN 80 for domestic needs with a capacity of 50,000 tons/year which later the SPAN 80 surfactant product besides being used for the needs of the nano asphalt manufacturing process can also be sold to meet market needs. The location of this factory is in the Industrial Area of Buton Regency, Southeast Sulawesi. The location is based on proximity to raw materials spread across Buton Island in the form of abundant Abuton rocks, ease of transportation and target market. PT XYZ operates 330 days a year with 15 days of shutdown and maintenance and the factory operates 24 hours every day. The surfactant used is sorbitan monooleate with raw materials Sorbitol and Oleic Acid with the help of a catalyst. The process for making surfactants uses the esterification method according to the International Process Plan 2009. This method is used because the process occurs at low atmospheric pressure and temperature so that the energy used is not too large. Whereas for the process of making nanoasphalt from asbuton using diesel solvent and additional additives in the form of rubber rubber. There are 3 main sources of factory profits, namely from the sale of nanoasphalt, surfactants and residues. From the results of the economic analysis, the value of ROI (29.88%) > Marr (14%) is obtained. PP < PAcceptable where PAcceptable is 4.95 years while the PP of this factory is 4.27 years. The IRR value for this factory is greater than the interest rate, the IRR value obtained is 30.95% while the interest rate is 6.38%. Then for the PV value at the end of the project life is greater than zero. The PV value obtained at the end of the project life is 547,309,577.58. Based on the economic analysis, PT XYZ is feasible to be established. Abstrak PT XYZ merupakan perusahaan yang memproduksi nanoaspal dari asbuton dengan menggunakan surfaktan Sorbitan Monooleat (SPAN 80). Sebagai salah satu pelopor industri nanoaspal di Indonesia, untuk memenuhi kebutuhan nanoaspal dalam negeri dengan kapasitas yang dirancang sebesar 80.000 ton/tahun. Selain membuat Nanoaspal sebagai produk utama, PT XYZ juga menyediakan SPAN 80 untuk kebutuhan dalam negeri dengan kapasitas sebesar 50.000 ton/tahun yang nantinya produk surfaktan SPAN 80 selain digunakan untuk kebuthan proses pembuatan nano aspal juga dapat dijual guna memenuhi kebutuhan pasar. Lokasi pabrik ini berada di Kawasan Industri Kabupaten Buton, Sulawesi Tenggara. Lokasi tersebut didasarkan karena dekat dengan raw material yang tersebar di pulau Buton berupa batuan Abuton yang melimpah , kemudahan transportasi dan target pasar. PT XYZ beroperasi selama 330 hari dalam satu tahun dengan waktu shutdown dan maintenance selama 15 hari dan setiap harinya pabrik beroperasi selama 24 jam. Surfaktan yang digunakan berupa sorbitan monooleat dengan bahan baku Sorbitol dan Asam Oleat dengan bantuan katalis. Proses pembuatan surfaktan menggunakan metode esterifikasi menurut International Process Plan 2009. Metode tersebut digunakan karena proses yang terjadi pada tekanan atmosferik dan temperatur yang rendah sehingga energy yang digunakan tidak terlalu besar. Sedangkan untuk proses pembuatan nanoaspal dari asbuton menggunakan pelarut solar dan tambahan bahan aditif berupa karet Rubber. Terdapat 3 sumber utama keuntungan pabrik, yaitu dari penjualan nanoaspal, surfaktan dan residu. Dari hasil analisis ekonomi diperoleh nilai ROI (29,88%) > Marr (14%). PP < PPacceptable dimana PPacceptable sebesar 4,95 tahun sedangkan PP pabrik ini 4,27 tahun. Untuk nilai IRR pabrik ini lebih besar dibanding nilai suku bunga, nilai IRR yang didapat sebesar 30,95% sedangkan suku bunga 6,38%. Lalu untuk nilai PV diakhir umur proyeknya lebih besar dari nol. Nilai PV yang diperoleh diakhir umur proyek sebesar 547.309.577,58. Berdasarkan analisis ekonomi tersebut maka PT XYZ layak untuk didirikan.